Personal Vocabulary Notes (PVN) Method in Enriching the Students’ Vocabulary - Hamdi Nur, Rapi (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
This study aimed to investigate the effectiveness of using Personal Vocabulary Notes (PVN) in enriching the vocabulary of students at MAN 1 Mamuju. The research focused on two main questions: (1) How does the PVN method improve students’ vocabulary in terms of nouns? and (2) How does the PVN method improve students’ vocabulary in terms of verbs? The research was conducted through Classroom Action Research (CAR) with two cycles, each consisting of four meetings. Data were collected using vocabulary tests and observation sheets, involving 30 students from class A. The findings revealed a significant improvement in students’ vocabulary between cycle I and cycle II. Students showed greater progress in the second cycle, with the mean score rising from 67.05% in cycle I to 85.90% in cycle II, which falls under the “very good” category. These results indicate that the PVN method effectively enhanced students’ vocabulary. Initially, their vocabulary level was categorized as low, but by the end of cycle II, it had reached a high level.